Estudo de arranjo granulométrico e condições operacionais de pré-filtração seguida de filtração lenta - Lunardi, Samuel (2021)
Pre-filtration followed by slow filtration is highlighted by its ability to promote greater efficiency in removing variable physical characteristics from raw water. The study aimed to apply different filtration rates to a pre-filter configuration as a form of protection for slow filters (d10=0.46 mm). The system consisted of a pre-filtration pilot with particle size characteristics of fast filters, followed by a double layer slow filtration pilot composed of anthracite coal (d10=0.27 mm) and sand (d10=0.26 mm). The operation took place in two phases, differentiated by the filtration rates applied to the columns, with only 11m³/m².d in Phase 1, and in Phase 2, the rates of 11m³/m².d and 5.5 m³/m² being used simultaneously .d in Phase 2. After the completion of the races, the pilots had their cleaning performed by sweeping. During the first phase, the system operated for 69 days, taking six rounds of filtration in the pre-filter (PF) with a duration of between 5 and 21 days. Moreover, four filtration lines in the slow filter (F) lasting between 7 and 27 days. In the second phase, a set of Pre-filter (PF1) and Slow filter (F1) with a filtration rate of 11 m³/m²d and a set of Pre-filter (PF2) and Filter (F2) with a rate of filtration of 5.5 m³/m².d. In this phase, the pilots operated for 41 days, with four complete filtration runs and one incomplete for the PF1(11m³/m².d), lasting between 6 and 18 days, in addition to 1 incomplete run for F1 (11m³/m².d ) lasting 41 days. In the second phase, the PF2 (5.5m³/m².d) obtained three filtration rows lasting from 7 to 21 days and one incomplete row for the F2 (5.5m³/m².d) lasting 41 days. Phase 1 (11m³/m².d) presented an average turbidity removal of 45.6% in the PF, and for the complete system, 54% of average turbidity removal was obtained. The average removal of total coliforms and E. coli was above 99%. As for Phase 2, the average results obtained for turbidity removal in PF1 (11m³/m².d) were 84.7% and 90% for the complete system (11m³/m².d). The PF2 (5.5m³/m².d) promoted an average removal of 84.5% of turbidity, while the complete system (5.5m³/m².d) removed an average of 90.2% of the turbidity of the raw water. The average removal of total coliforms and E. coli were above 90%. At the end of the study, it is concluded that pre-filtration systems promote prior removal of physical aspects of the water, regardless of the filtration rate applied to the system. Different filtration rates provide different clogging processes in the system. The density of the filter material can influence the efficiency of removing physical aspects from the water. The cleaning method by scraping did not prove to be the most suitable for such Pre-filters and Slow Filters configurations.